Development of A STEM-Based Mathematics E-Module to Improve 4C Skills of Vocational Students - Nisa Vebriani; Usmeldi Usmeldi; Dedy Irfan; Ta’ali Ta’ali (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This research aims to develop a STEM (Science, Technology, Engineering, and Mathematics) based mathematics e-module that is valid, practical and effective in improving vocational students' 4C (Critical Thinking, Communication, Collaboration, Creativity) skills. The research uses the Plomp development model with stages: 1) preliminary research, 2) prototyping phase, and 3) assessment phase. Research data collection uses questionnaire sheets, interviews, checklists, validation sheets, and test sheets. Product validation includes media, material, and language expert validation. The data collected was then analyzed quantitatively and qualitatively. The research results show that STEM-based mathematics e-modules are valid, practical and effective. Valid in terms of appropriateness of content, didactics/presentation, graphics, and language. Practical in terms of readability and clarity of material, ease of use, attractiveness and suitability of time allocation. Furthermore, it is said to be effective because the use of this e-module in the learning process can improve students' 4C skills with an N-gain of 0.58 on medium criteria and an average 4C skills assessment result of 79.00 with a good predicate.